SOCIOLINGUISTICS, COGNITIVISM, AND DISCURSIVE PSYCHOLOGYL - Potter, Jonathan; Edwards, Derek (International Journal of English Studies, 2003)
This paper addresses the broad question of how work in sociolinguistics should be related to social theory, and in particular the assumptions about cognition that can underpin that relation. A discursive psychological approach to issues of cognition is pressed and illustrated by a reworking of Stubb’s review of work on language and cognition. A discursive psychological approach is offered to the topics of racist discourse, courtroom interaction, scientific writing, and sexism. Discursive psychology rejects the approach to ’cognition’ as a collection of more or less stable inner entities and processes. Instead the focus is on the way ’mental phenomena’ are both constructed and oriented to in people’s practices.